Completion of an Enhanced Recovery Program in a Pediatric Ambulatory Surgery Center: A Quality Improvement Initiative. (16th November 2022) - Martin, Lynn D.; Chiem, Jennifer L.; Hansen, Elizabeth E.; Low, Daniel K.; Reece, Kayla; Casey, Corrie; Wingate, Christina S.; Bezzo, Leah K.; Merguerian, Paul A.; Parikh, Sanjay R.; Susarla, Srinivas M.; O'Reilly-Shah, Vikas N.
Abstract : BACKGROUND: Enhanced Recovery After Surgery (ERAS) was first established in 2001 focusing on recovery from complex surgical procedures in adults and recently expanded to ambulatory surgery. The evidence for ERAS in children is limited. In 2018, recognized experts began developing needed pediatric evidence. Center-wide efforts involving all ambulatory surgical patients and procedures have not previously been described. METHODS: A comprehensive assessment and gap analysis of ERAS elements in our ambulatory center identified 11 of 19 existing elements. The leadership committed to implementing an Enhanced Recovery Program (ERP) to improve existing elements and close as many remaining gaps as possible. A quality improvement (QI) team was launched to improve 5 existing ERP elements and to introduce 6 new elements (target 17/19 ERP elements). The project plan was broken into 1 preparation phase to collect baseline data and 3 implementation phases to enhance existing and implement new elements. Statistical process control methodology was used. Team countermeasures were based on available evidence. A consensus process was used to resolve disagreement. Monthly meetings were held to share real-time data, gather new feedback, and modify countermeasure plans as needed. The primary outcome measure selected was mean postanesthesia care unit (PACU) length of stay (LOS). Secondary outcomes measures were mean maximum pain score in PACU and patient/family satisfaction scores. RESULTS: The team had expanded the pool of active ERP elements from 11 to 16 of 19. The mean PACU LOS demonstrated significant reduction (early in phase 1 and again in phase 3). No change was seen for the mean maximum pain score in PACU or surgical complication rates. Patient/family satisfaction scores were high and sustained throughout the period of study (91.1% ± 5.7%). Patient/family and provider engagement/compliance were high. CONCLUSIONS: This QI project demonstrated the feasibility of pediatric ERP in an ambulatory surgical setting. Furthermore, a center-wide approach was shown to be possible. Additional studies are needed to determine the relevance of this project to other institutions.